Achieving excellence through information literacy as part of innovative curriculum - Raja Yaacob, Raja Abdullah; Raja Yaacob, Raja Ahmad Iskandar; Jusoff, Kamaruzaman (ERM Publications, 2011)
A great responsibility facing education today is to develop students with information literacy while pursuing their education and extend it further in their workplace. In order for today's students to excel in the 21st century, they must be able to acquire, evaluate, and use and present information effectively. They must become information literate workers, teachers, facilitators and coachers. Information literacy skills allow the problem solving, critical and creative thinking, decision making, and cooperative learning that prepare students for the challenges in society. Information literacy leads to skilful, responsible thinking that facilitates good judgement because it relies on criteria, is self-correcting and is sensitive to context. It helps growth of individuals through a number of methods, programmes and techniques. It would be useful if the educational incorporate these elements since the elementary stage so that by the time their reach the college and university level, they have acquired the reading and information skills much required in the current information and knowledge era.